Distribution and sources of PAHs using three pine species along the Ebro River - Nuno Ratola (2012)
Needles of three pine species (Pinus halepensis, Pinus pinea and Pinus nigra) were analysed to assess the occurrence of polycyclic aromatic hydrocarbons (PAHs) in 34 sites located throughout the Ebro River, in Northeast Spain. Overall, the concentration varied between 55 and 808 ng g (-aEuro parts per thousand 1) (dry weight). The three- and four-ring PAHs were the most representative, with phenanthrene having 43% of the total PAH load and naphthalene showing a high incidence in rural areas. Despite matrix apparent similarities, P. halepensis needles revealed higher entrapment levels than P. nigra and P. pinea, the latter showing the lowest levels. The assessment of possible sources using PAH ratios (phenanthrene/anthracene and fluoranthene/pyrene) did not reveal a clear tendency regarding the distinction of petrogenic and pyrogenic sources in general, reflecting heterogeneous sources of PAHs in the Ebro area.